'Caring and connected': technology and social worker self-care. Issue 3 (3rd July 2022) - Harris, Sera; Stout, Brian
ABSTRACT: This article outlines social work practitioners' understandings and practices of self-care, which consider the influence of technology. As part of an exploratory study on the use and experiences of technology by Australian social work practitioners, we examined implications for worker self-care. The study found that technology presents unique challenges and opportunities for self-care as social workers straddled multiple and contradictory conceptualisations of technology in the field. The use of technology raised mixed understandings of self-care, with social workers outlining the need for self-care to protect them from organisational reach and as a mechanism or space for self-care itself. The study findings highlight the need to consider technology in the understandings and practices of self-care for social workers.